2015
DOI: 10.1038/npjschz.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

The proteome of schizophrenia

Abstract: On observing schizophrenia from a clinical point of view up to its molecular basis, one may conclude that this is likely to be one of the most complex human disorders to be characterized in all aspects. Such complexity is the reflex of an intricate combination of genetic and environmental components that influence brain functions since pre-natal neurodevelopment, passing by brain maturation, up to the onset of disease and disease establishment. The perfect function of tissues, organs, systems, and finally the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 157 publications
(261 reference statements)
2
67
1
3
Order By: Relevance
“…These studies have also identified a large number of differentially expressed proteins associated with energy metabolism, the cytoskeleton, and cell signaling [12]. Since these pathways are mainly in the cytoplasm, the present study used an enrichment method to obtain only the soluble fraction of the CC proteome and pinpoints exactly differences in the expression of glial proteins, because the CC is predominantly a white matter region.…”
Section: Introductionmentioning
confidence: 98%
“…These studies have also identified a large number of differentially expressed proteins associated with energy metabolism, the cytoskeleton, and cell signaling [12]. Since these pathways are mainly in the cytoplasm, the present study used an enrichment method to obtain only the soluble fraction of the CC proteome and pinpoints exactly differences in the expression of glial proteins, because the CC is predominantly a white matter region.…”
Section: Introductionmentioning
confidence: 98%
“…It has been demonstrated that there are dynamic changes correlating changes in brain and blood and vice-versa [47,74], and, in the case of SCZ, some changes in hormones, cytokines or growth factors can be replicated both in brain and blood stream [74,76].…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%
“…Nonetheless, and although very informative, post-mortem brain tissue has its drawbacks, as the susceptibility of confounding factor, namely medication or age and chronicity of the disease, besides the fact that the tissue is static, with no possibilities of being manipulated, disturbed or having longitudinal samplings [46,47]. Thus, current proteomic studies have been focusing in peripheral tissues or fluids, and integrating all these analyses a more complete picture of the disease is expected to emerge in what concerns onset, progression and responsiveness [47].…”
Section: Proteomics Contribution For Schizophrenia's Biomarker Researchmentioning
confidence: 99%
“…Due to its capacity for profiling large numbers of proteins simultaneously, proteomics is currently one of the main techniques used to understand biochemical pathways and, consequently, multifactorial disorders such as SCZ [6]. In the last 2 decades, proteomics has contributed to a growing understanding of SCZ, and a number of such studies investigating this disorder have been published revealing alterations in several biochemical pathways of the central nervous system [5]. However, it is important to note that in proteomic analyses of whole tissues, it is often not possible to detect proteins that are present at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high prevalence and severity, little is known about the biochemical mechanisms involved in its development or progression, and so there are few established molecular diagnoses or specific treatments. Thus, there is currently a great interest in obtaining new knowledge about the disease and, in this arena, proteomic analyses have already yielded promising results and opened up new avenues of research [5]. …”
Section: Introductionmentioning
confidence: 99%